Interactions between kappa-carrageenan and some surfactants in the bulk solution and at the surface of alumina. (5th June 2015) - Grządka, E.
Highlights: Kappa-carrageenan (Carr) forms strong electrostatic complexes with CTAB. Formation of Carr/CTAB complexes causes the increase of Carr adsorption on Al2 O3 . Kappa-carrageenan forms week complexes with TX-100. Kappa-carrageenan does not form complexes with SDS. Abstract: The interactions between surfactants (SDS, CTAB, TX-100 or their equimolar mixtures) and kappa-carrageenan (Carr) in the bulk solution and at the surface of alumina were determined using the surface tension and the spectrophotometric adsorption measurements. The obtained results show that Carr has the ability to create the multilayer complexes with CTAB, TX-100 and the equimolar mixtures of surfactants (CTAB/TX-100), but does not interact with SDS. The created complexes are electrostatic (with CTAB) or they are of different mechanisms such as the hydrogen bonding or the acid–base interactions (with TX-100). The electrokinetic measurements (the surface charge density and the zeta potential) allow to analyze the structure of the adsorption layer: polymer/surfactant/metal oxide. It turned out that the macromolecules of Carr are directly bonded to the surface whereas the surfactants are present in the upper parts of the electrical double layer.